2000
DOI: 10.1176/appi.ajp.157.7.1170
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Famine and Brain Morphology in Schizophrenia

Abstract: Nutritional deficiency during the first trimester of gestation resulted in an increase in clinical brain abnormalities and was associated with aberrant early brain development in patients with schizophrenia. Stunted brain development secondary to factors that affect brain growth during the first trimester of gestation may thus be a potential risk factor for developing schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
70
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(77 citation statements)
references
References 8 publications
4
70
1
2
Order By: Relevance
“…However, beyond global sparing, numerous studies in various mammalian models depict a complex picture with NR-induced structural alterations, the nature and strength of which are region-specific (Morgane et al, 2002; Alamy and Bengelloun, 2012). Moreover, while some of these alterations recover on return to a normal diet after birth, growing evidence suggests that early nutritional stress leaves permanent traces responsible for abnormal cognitive, behavioral, and psychiatric outcomes later in life (Hulshoff Pol et al, 2000; Rehn et al, 2004; Roza et al, 2008; De Rooij et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…However, beyond global sparing, numerous studies in various mammalian models depict a complex picture with NR-induced structural alterations, the nature and strength of which are region-specific (Morgane et al, 2002; Alamy and Bengelloun, 2012). Moreover, while some of these alterations recover on return to a normal diet after birth, growing evidence suggests that early nutritional stress leaves permanent traces responsible for abnormal cognitive, behavioral, and psychiatric outcomes later in life (Hulshoff Pol et al, 2000; Rehn et al, 2004; Roza et al, 2008; De Rooij et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…A common phenotype of these disorders is impaired cognitive function (Arnsten 2009; Douglas and Porter 2009) with impaired executive function being among the premorbid cognitive deficits preceding onset of these disorders (Kates 2010). Several classes of prenatal factors have been implicated as adversely affecting brain development including premature birth (Huppi et al 1998; Peterson et al 2000; Peterson et al 2003; Beauchamp et al 2008; Davis et al 2011a), exposure to obstetric risk conditions such as infection (Brown et al 2009; Sorensen et al 2009), maternal undernutrition (Hulshoff Pol et al 2000), and unhealthy maternal behaviors such as smoking, alcohol, or drug use (Sowell et al 2008; Lotfipour et al 2009; Thompson et al 2009). Little is known about the consequences of brain development of fetal exposure to prenatal maternal psychosocial stress.…”
Section: Introductionmentioning
confidence: 99%
“…The IGF2 locus plays a key role in development and growth (Delaval, Wagschal and Feil 2006) and defects in methylation at this locus are known to contribute to several imprinting-related disorders, such as Silver-Russell syndrome and Beckwith-Wiedemann syndrome (Bartholdi et al 2009; Riccio et al 2009). Notably, brain weight in males is positively correlated with DNA methylation at IGF2 (Pidsley, Dempster and Mill 2010); and, in turn, low brain weight has been associated with schizophrenia (Harrison, Freemantle and Geddes 2003), including within the Dutch Hunger Winter cohort (Hulshoff Pol et al 2000). Together, these observations suggest that social exposures may influence DNA methylation in a manner salient to mental health; however, studies explicitly testing this hypothesis have, to our knowledge, yet to be reported.…”
Section: Introductionmentioning
confidence: 99%